PERPEKTIF NILAI BERBASIS BUDAYA LOKAL PADA CREDIT UNION SAUAN SIBARRUNG - Pasoloran, Oktavianus; Topayung, Sri Eva; Tanamal, Cherly E. (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2023)
This study aimed to understand how activists and members of the Sauan Sibarrung Credit Union interpret core values in the perspective of Toraja culture as a container (jars containing gold = saun sibarrung) that can be a source of welfare (endless water source = gori-gori tang ma'ti) for members and communities. This research uses a qualitative approach with phenomenological methods. The results showed that (1) the eight core values in the Sauan Sibarrung Credit Union are sangka' (teachings, general truths) which are also the philosophy of life of the Torajan people, where people live in rules, fight for the integrity of life, act wisely, lovingly and solidly, care for the environment, hard work and tenacity, and are based on the belief of faith to live true and whole together with other creations of God, (2) The eight core values become a model of values, as a credit union culture, and form the basis of the strategy and policy for the development of the Sauan Sibarrung Credit Union program as well as guidelines for all behavior of individuals, organizations, and communities